Mempersenjatai Konflik Yaman: Menelaah Kesepakatan Hubungan Bersenjata AS-Saudi, Kapitalisme Modern, dan Peperangan Berkepanjangan - Pramudia, Putu Shangrina (PT Elaborium Elevasi Indonesia, 2024)
With the massive flow of globalization, the last two centuries have seen the rise of the private defence industry, which offers a range of services and equipment needed in the military domain. These industries have had a significant influence in shaping the international political- economic order and in the context of global capitalism in the contemporary era. The private defence industry further benefits from the conflict, as was the case in the Yemen Civil War. The arms exports carried out by the US to Saudi and its coalition has been responsible for continuing the most severe humanitarian crisis in the world today. Seeing the chaotic situation, the US did not stop the arms deal with the Saudis but instead strengthened relations and multiplied the value of the arms deal. This paper uses qualitative research methods. With the conceptions of the Military-Industrial Complex (MIC) and the Defence Iron Triangle (DIT), the results indicate that the rise of the private defence industry has succeeded in creating opportunities for modern capitalism and a network of interest groups that have benefited from the Yemen Civil War. Thus, defence contractors, legislators, and executive bodies are trying to perpetuate arms deals, regardless of the never-ending war that becomes the consequence.